High resolution ultra sound and color Doppler in evaluation of thyroid nodule with fine needle aspiration cytology correlation - Chaudhary, Suman; Verma, Anand Prakash; Mishra, Hemant K. (International Journal of Research in Medical Sciences, 2016)
Background: Thyroid gland is the first to develop in fetal life and is largest of all the endocrine glands. It is superficial in location which helps in its excellent visualization of normal anatomy and pathologic condition by high resolution real time grey scale sonography. The purpose of this study was to evaluate the usage of grey scale ultrasound and color Doppler with FNAC correlation for differentiation of benign and malignant thyroid nodule. Methods: This prospective study was carried out on sixteen patients who came to our department from period of 1 February to 31 march 2016.Grey scale ultrasound of neck and Doppler followed by USG guided FNAC of thyroid swelling was done. Results: Out of 16 cases, 3 were malignant, 10 were benign, and 3 were indeterminate. One case was diagnosed as benign lesion on sono which came out to be malignant on pathology as follicular carcinoma. The cases were presented as hypoechoic lesion with regular margins with peripheral and internal vascularity. Due to well defined margins it was diagnosed as benign adenoma but turned out to be malignant on pathology as follicular carcinoma. Colloid goiter was most common presentation on ultrasound and it showed wide spectrum of appearance, majority being nodular with anechoic echotexture. Conclusions: High resolution grey scale ultra sound with color Doppler has emerged as initial modality of choice for evaluating the patient with thyroid enlargement.